Nuclear medicine imaging for bone metastases assessment: what else besides bone scintigraphy in the era of personalized medicine? - Ouvrard, Eric; Kaseb, Ashjan; Poterszman, Nathan; Porot, Clémence; Somme, Francois; Imperiale, Alessio (Frontiers in Medicine, 2024)
Accurate detection and reliable assessment of therapeutic responses in bone metastases are imperative for guiding treatment decisions, preserving quality of life, and ultimately enhancing overall survival. Nuclear imaging has historically played a pivotal role in this realm, offering a diverse range of radiotracers and imaging modalities. While the conventional bone scan using 99m Tc marked bisphosphonates has remained widely utilized, its diagnostic performance is hindered by certain limitations. Positron emission tomography, particularly when coupled with computed tomography, provides improved spatial resolution and diagnostic performance with various pathology-specific radiotracers. This review aims to evaluate the performance of different nuclear imaging modalities in clinical practice for detecting and monitoring the therapeutic responses in bone metastases of diverse origins, addressing their limitations and implications for image interpretation.